Tren Bibliometrik CLIL pada Pembelajaran BIPA Pemetaan Tren Publikasi, Kolaborasi, dan Sitasi - Rully Khairul Anwar; Yunus Winoto; Khansa Wynonna Wijayakusumah (Tadris Bahasa Indonesia, Fakultas Tarbiyah, Institut Agama Islam Negeri Madura, 2026)
Increased global attention to BIPA has encouraged the use of the Content Language Integrated Learning (CLIL) approach, but research on this topic is considered inconsistent and individualistic. This study aims to map publication trends, collaboration patterns, and the impact of CLIL research citations on BIPA using bibliometric analysis assisted by R Studio Biblioshiny. The results of the analysis show a significant surge in publications in 2021 due to pandemic adaptation, with Indonesia identified as a major knowledge center. However, critical findings reveal a clear gap in international collaboration, with publications dominated by Single Country Publications (SCP). This indicates a lack of research partnerships between Indonesian researchers and other countries. The study concludes that there is a need to transform individual initiatives into a strategic national agenda. Implicitly, policymakers need to prioritize cross-border research collaboration as an instrument of language diplomacy to strengthen the relevance and existence of BIPA globally.